2023
DOI: 10.1136/bmjopen-2022-066757
|View full text |Cite
|
Sign up to set email alerts
|

Understanding medication safety involving patient transfer from intensive care to hospital ward: a qualitative sociotechnical factor study

Abstract: ObjectiveTo understand the sociotechnical factors affecting medication safety when intensive care patients are transferred to a hospital ward. Consideration of these medication safety factors would provide a theoretical basis, on which future interventions can be developed and evaluated to improve patient care.DesignQualitative study using semistructured interviews of intensive care and hospital ward-based healthcare professionals. Transcripts were anonymised prior to thematic analysis using the London Protoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 57 publications
1
0
0
Order By: Relevance
“…A recent qualitative study from adult ICU settings identified 13 sociotechnical factors impacting medication safety in patients transitioning from ICU to ward environments. 14 These factors, grouped into five themes, align with our study’s findings, including the importance of diverse professional expertise, written communication, tool and technology availability, beliefs about consequences of medication errors and physical environment factors. However, the study also discovered additional factors not found in our research, such as the positive effect of patient and family involvement post-ICU discharge, and the role of prescription annotations.…”
Section: Discussionsupporting
confidence: 69%
“…A recent qualitative study from adult ICU settings identified 13 sociotechnical factors impacting medication safety in patients transitioning from ICU to ward environments. 14 These factors, grouped into five themes, align with our study’s findings, including the importance of diverse professional expertise, written communication, tool and technology availability, beliefs about consequences of medication errors and physical environment factors. However, the study also discovered additional factors not found in our research, such as the positive effect of patient and family involvement post-ICU discharge, and the role of prescription annotations.…”
Section: Discussionsupporting
confidence: 69%
“…Patients and family members concurred with HCPs that when acutely ill, patients often were unable to have an active role in decisions about their medications. 18 During this period, the patient advocacy role of family members was vital. Manias et al 30 also identified the important role family members have in medication safety in an observational study of communication between intensive care HCPs and patients and family members.…”
Section: Discussionmentioning
confidence: 99%
“… 16 , 17 In contrast, HCPs perceive barriers to routine engagement and information provision for patients and families after a critical care episode. 14 , 18 HCPs’ and public representatives’ beliefs can differ on the importance of medication information provision to improve medication safety, 15 contributing to patient reports of inadequate communication, predisposing them to anxiety or distress on transition of care. 19 …”
mentioning
confidence: 99%